Socio-Economic Determinants of Students’ Academic Achievement in Building Technology in North-Central Nigeria - Yahaya Ibn Salihu; Nordin Safarin Mohd (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
This study investigated socio-economic determinants of students’ academic achievement in building technology in North-central Nigeria. It was a quest to probe into the incessant cases of students’ poor achievement in building technology to identify students’ determining factors. Survey research design was adopted in carrying out the study. Data were collected from 113 students on their socioeconomic attributes and their academic record. Data were analysed using descriptive and inferential statistics such as frequency, percentage, mean and multiple regression analysis. The results of the study showed that building technology education in Nigeria is male dominated and majority of colleges of education students in North-central Nigeria are under 20 years. Socio-economic determinants of students’ academic achievement in building technology include gender, age, study hours, family size, stipends per month, group reading, students’ health status, credit pass in SSCE and truancy. The challenges facing building technology students in the study area include epileptic power supply, inadequate ICTs, lack of functional building technology workshop among others.